Quality of Life and the Contributing Factors among Elderly in Rural Areas in Yogyakarta - Ani Mashunatul Mahmudah; Supriyadi; Suthida Intaraphet; Khannistha Mahem; Kunlayarat Kadsanit; Pawintra Manadee; Chanif Kurniasari; Kurniati, Fitri Dian (Universitas Airlangga, 2023)
Background: Older people are a high-risk population with decreased health status and quality of life (QoL). There are various conditions that can affect the QoL in older people. QoL in older people requires cooperation from various parties including family members, health workers, and local government to improve it. Understanding factors contributing to QoL among older people is significantly important. Aims: The research objective was to analyze the relationship between age, gender, education, and occupation status with QoL in older people. Methods: A cross-sectional design was used to identify related factors contributing to QoL among older people. QoL was assessed by using SF-36. This instrument contains eight subgroups namely role-physical, physical function, mental health, bodily pain, social functioning, role-emotional, general health, and vitality. Descriptive statistics and correlation coefficients were used in reporting and analyzing the data. The research was conducted from December 2019 to June 2020 in Pleret, Yogyakarta. The sample was collected by simple random sampling resulting in a total of 102 older people. Results: Factors significantly related to the QoL subgroup in this study were as follows. Age (p<0.001) and occupational status (p<0.001) related to physical function, gender (p<0.05) related to mental health, age (p<0.05) and educational level (p<0.05) related to roleemotional and gender (p<0.05) related to general health. Conclusion: This study identified factors that contributed to the QoL in older people including age, gender, educational level, and occupational status. A more in-depth investigation is recommended to determine the other QoL contributing factors among older people.